Sistematización de la experiencia de medición de factores de riesgo psicosocial y propuesta de un plan mejora, al personal administrativo y operativo de una empresa generadora de energía eléctrica ubicada en la ciudad de Quito provincia de Pichincha en el periodo de febrero a noviembre del 2017. - Chavisnan Nazate, Jonathan Jairo (2018)
The present project belongs to the Labor Safety and Occupational Health field. It was developed in an Ecuadorian electric company which is located in the city of Quito, province of Pichincha, during the period of ten months going from February until November 2017. In the study process was involved the participation of 120 collaborators corresponding to administration, maintenance and operation areas. Being an institution with extensive working population a sample was established, working in conjunction with the Department of Occupational health, industrial safety and human talent. The main target of the intervention project was to measure the rating of psycho-social risk factors from the employees through a tool called Factores Psicosociales versión 3.1(F-PSICO V 3.1), which is a test with 44 questions. In addition its results allowed to develop an improving plan, with the purpose of promoting prevention spaces to save the physical, psychic and social health from the employees. The structure of study included an initial diagnosis about the most common exposition risks inside the company. Likewise it considers topics related to the performance, establishing the line bases for future studies. In spite of the ideological political changes that the country has been going through during the project, the labor population for whom it was directed, and the professionals answered in a positive way accomplishing the main goal which includes the commitment, responsibility and motivation from the collaborators